The Selective Catalytic Reduction of Nitric Oxide with Methane over La2O3–CaO Systems: Synergistic Effects and Surface Reactivity Studies of NO, CH4, O2, and CO2 by Transient Techniques - Costa, Costas; Anastasiadou, T.; Efstathiou, A. M. (My University, 2000)
Dispersing La2O3 crystallites in a 5 wt% La2O3–CaO mixed oxide system significantly enhances the intrinsic rate of NO reduction by CH4 in the presence of 5% O2 at 550°C compared to pure La2O3 and CaO phases. A synergistic effect between La2O3 and CaO crystallites due to doping of lanthana with Ca2+ ions at 800°C is largely responsible for the observed catalytic behavior. Support of this view was provided by photoluminescence studies and a large number of transient experiments for determining the surface reactivity of x wt% La2O3/CaO (x wt%=0, 5, 80, 100) solids toward NO, CH4, O2, and CO2. The intrinsic site reactivity of the 5 wt% La2O3–CaO system at 550°C (TOF=6×10−3 s−1) competes favorably with that of other similar oxides for the same reaction reported in the literature. X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques have been used for crystal phases and particle morphology characterization of the x wt% La2O3/CaO mixed oxide system. The information obtained from the XRD measurements was related to that obtained from the surface transient reactivity studies. By the addition of La2O3 crystallites to CaO crystallites in a wet mixing procedure followed by calcination in air at 800°C, results in dramatic changes in the chemisorptive properties (amount and bond strength) of NO, O2, and CO2 compared to the case of pure oxide phases. Pretreatment of the catalyst surface with H2 or CH4 was found to strongly affect the amount of NO chemisorption and the kinetics of its desorption. These alterations were found to strongly depend on catalyst composition.
Keywords: Lanthana; Calcium oxide; CO2 TPD; NO reduction by CH4; NO TPD; O2 TPD; Transient methods